Performance of growing crossbred (Bos taurus x Bos indicus) calves on grain replaced diet - MONDAL, B C; GARG, A K; KAMRA, D N; PATHAK, N N (The Indian Journal of Animal Sciences, 2014)
In a growth trial. 5 month-old male crossbred calves (30) were divided into 5 groups of 6 each on the basis of body weight. The calves in group 1 (control) were fed a standard concentrate mixture of crushed maize, groundnut-cake and wheat bran. The maize moiety was replaced with wheat bran at 50% level in groups 2 and 4 and 100% level in groups 3 and 5. Wheat straw was offered ad lib. in groups 1, 2 and 3, whereas, groups 4 and 5 received ad lib. sorghum green fodder. Diets in all the groups Were isonitrogenous. Mean daily gains for 21 weeks duration were 415,416,410, 616 and 580 g with a DMI of 83.3'6, 83.72, 83.23,92.56 and 92.74 g per kg Wo.75 in groups 1,2,3,4 and 5, respectively,which was significantly higher in green fodder fed groups. FCB was significantly better in green fodder fed groupS. The source of roughage influenced the nutrient utilization but grain restriction did not. Grain sparing effectofwheat bran was observed in straw fed and green fodder fed group. Scope of further improvement in body weight gain through replacement of straw with green fodder is prominent.